Pengaruh Gaya Kepemimpinan, Disiplin dan K3 terhadap Kepuasan Kerja Karyawan di PT Darmasindo Intikaret - Rahayu Rahayu; Winda Kristiyani Br Purba; Aisyah Siregar; Willy Cahyadi (Jurnal Riset Ekonomi dan Akuntansi, 2026)
The rubber processing manufacturing company PT Darmasindo Intikaret Tebing Tinggi is encountering more and more intense competition. So, managing human resources, the company's most valuable asset, is a top priority alongside meeting financial and operational goals. In human resource management, employee happiness is a key performance measure. Leadership style, discipline, and K3 are all variables that this study hopes to identify and examine in some detail. This research falls under the category of development studies and employs a quantitative methodology. This research makes use of both primary and secondary sources for its data. Findings from both primary and secondary sources are used into this research. People who work in production at PT. Darmasindo Intikaret were the subjects of this research. According to the results of the complete sampling method, the milling production staff consists of 34 individuals. In this study, the entire population is employed as a sample. The data analysis techniques utilised in this study included reliability and validity tests, tests for classical assumptions like normality and multicollinearity and heteroscedasticity, and tests for multiple regression, determination coefficients, and hypotheses like the F and T tests. Leadership style significantly and positively affects employee job satisfaction, according to the study's results. There is a favourable and statistically significant relationship between discipline and employee job satisfaction, and K3 is no exception. Employees' happiness on the job is influenced by a number of factors, including leadership style, discipline, and K3. The significance of enhancing the quality of leadership style, discipline, and 3 in boosting employee job satisfaction in a firm, particularly manufacturing companies, can be demonstrated by doing this study.